2017
DOI: 10.1158/1078-0432.ccr-17-0242
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Inhibits Cancer Metastasis and Angiogenesis via Targeting Heparanase

Abstract: Purpose: Recent epidemiological and clinical studies have suggested the benefit of aspirin for patients with cancer, which inspired increasing efforts to demonstrate the anticancer ability of aspirin and reveal the molecular mechanisms behind. Nevertheless, the anticancer activity and related mechanisms of aspirin remain largely unknown. This study aimed to confirm this observation, and more importantly, to investigate the potential target contributed to the anticancer of aspirin.Experimental Design: A homogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 47 publications
4
64
0
5
Order By: Relevance
“…MTT assays showed the compounds to have low cytotoxicity at this concentration (Figure S33). Similar phenomena were also observed for SA and As , consistent with literature reports that anti‐angiogenesis is involved in the anticancer properties of As …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…MTT assays showed the compounds to have low cytotoxicity at this concentration (Figure S33). Similar phenomena were also observed for SA and As , consistent with literature reports that anti‐angiogenesis is involved in the anticancer properties of As …”
Section: Resultssupporting
confidence: 91%
“…Similarp henomena were also observed for SA and As,c onsistent with literature reports that anti-angiogenesis is involved in the anticancer properties of As. [59]…”
Section: Inhibition Of Metastasis-related Eventsmentioning
confidence: 99%
“…For the antiangiogenic effect, aspirin down-regulates heparanaserelated VEGF levels which decreases tumor angiogenetic activity. They further verified the binding sites for aspirin in heparanase as Lys159 and Glu225, which may propose new inhibitors of heparanase by binding to these two sites (60).…”
Section: Heparanasementioning
confidence: 69%
“…A recent study of Dai and her colleges suggested heparanase participating in the antitumor activity of aspirin through affecting the metastasis and angiogenesis of tumor cells (60).…”
Section: Heparanasementioning
confidence: 99%
“…Moreover, aspirin inhibits hydroxyacid‐oxoacidtranshydrogenase‐mediated production of (R)‐2‐hydroxyglutarate, a metabolite that promotes some kinds of tumors . A recent study demonstrates that aspirin inhibits cancer metastasis and angiogenesis via targeting heparanase . In addition, aspirin reportedly inhibits tumor growth and stemness in colorectal cancer by downregulating Nanog .…”
Section: Complex Mechanisms For the Anticancer Effects Of Aspirinmentioning
confidence: 99%